An Efficient Protocol for the Carbon–Sulfur Cross-Coupling of Sulfenyl Chlorides with Arylboronic Acids using a Palladium Catalyst - Gogoi, Prasanta; Kalita, Mukul; Barman, Pranjit (Synlett, 2014)
An efficient protocol for carbon–sulfur bond formation is developed, which involves the cross-coupling of sulfenyl chlorides and arylboronic acids catalyzed by a novel palladium–Schiff base complex. Good to high product yields, short reaction times, and mild reaction conditions are important features of this new method.
Keywords: arylboronic acids; sulfenyl chlorides; palladium catalysis